Genotype, Phenotype Characteristics and Long-Term Follow-Up of Patients with Vitamin D-Dependent Rickets Type IA: A Nationwide Multi-Centre Retrospective Cross-Sectional Study - Cayir, Atilla; Demirbilek, Huseyin; Turkyilmaz, Ayberk; Turan, Serap; Bereket, Abdullah; Darendeliler, Feyza; Ozkan, Behzat (Karger, 2025)
Introduction: Vitamin D-dependent rickets type IA (VDDR1A) is an autosomal recessive disorder characterized by defects in the biosynthesis of its active form 1,25-dihydroxyvitamin D due to mutations in the CYP27B1 gene, which encodes for 1 alpha-hydroxylase. The present study aimed to evaluate the clinical characteristics, molecular genetic aetiology, and long-term outcomes of a large nationwide cohort of children with VDDR1A from Turkey. Methods: In this multi-centre retrospective cross-sectional study, we collected clinical characteristics, laboratory features, molecular genetic analysis results, and long-term follow-up of a nationwide cohort of patients with VDDR1A using a web-based research network, CEDD-NET, for paediatric endocrinology research. Results: In total, 118 patients (57 F, 61 M) with VDDR1A were recruited. The median age of the diagnosis was 1.7 years (0.2-18.3 years). The most common presenting complaints were skeletal deformity (n = 61), short stature (n = 45), and delay in walking (n = 42). The most common mutation was a splice-donor-site mutation (c.195+2T>G) (n = 42), followed by a 7-bp duplication 1319-1325dupCCCACCC (Phe443Profs*24) (n = 25), and two missense mutations p.K192E (c.574A>G) (n = 17) and c.1474C>T (p.R492W) (n = 12). The novel c.195+2T>C and c.1215_1215+2delTGTinsCGA splice-site and c.1144C>A missense variants were firstly described in our cohort. Conclusion: The most common four mutations accounted for the underlying aetiology of VDDR1A in approximately 81% of the cohort, indicating Turkey may serve as a mutational hotspot or exhibit a founder effect for these variants. Our large cohort's results suggested no clear and clinically meaningful phenotype-genotype relationship in VDDR1A
Keywords: Vitamin D-dependent rickets type I; Congenital rickets; Children; CYP27B1 gene